NILAI-NILAI PENDIDIKAN RELIGIUS DALAM IBADAH SHALAT SANTRI PUTRI PONDOK PESANTREN AL-AZHAR KARANGPLOSO MALANG PERIODE 17 OKTOBER 2019-17 APRIL 2020 (STUDI KASUS DI PONDOK PESANTREN AL-AZHAR MALANG) - Iin indrawati; Ach Faisol; Adi sudrajat (VICRATINA, 2020)
Prayer is the second pillar of faith that is highly recommended to be carried out in congregation. Congregation is togetherness in carrying out a thing. From the background, the researcher has a research focus, about how the prayer activities in the female students of the Al-Azhar Karangploso Ponpes al-Azhar Malang scholarship program and what are the religious values contained in the activities of the Muslim students' prayer in the Al-Azhar Karangploso Islamic Boarding School Malang. The purpose of this study is to describe the activities of Muslim students' prayer in the Arabic scholarship program containing religious values in al-Azhar Karangploso Islamic Boarding School in Malang. To achieve the above objectives, researchers conducted a type of qualitative research, data collection procedures using observation methods, documentation of interviews, and so on. In this study, the al-Azhar Islamic boarding school required its students to perform the Fardhu prayer in congregation.